2018
DOI: 10.3389/fphys.2018.01673
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory, Taste, and Photo Sensory Receptors in Non-sensory Organs: It Just Makes Sense

Abstract: Sensory receptors that detect and respond to light, taste, and smell primarily belong to the G-protein-coupled receptor (GPCR) superfamily. In addition to their established roles in the nose, tongue, and eyes, these sensory GPCRs have been found in many ‘non-sensory' organs where they respond to different physicochemical stimuli, initiating signaling cascades in these extrasensory systems. For example, taste receptors in the airway, and photoreceptors in vascular smooth muscle cells, both cause smooth muscle r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 203 publications
(243 reference statements)
1
44
0
1
Order By: Relevance
“…The catalog of vertebrate tissues that have been found to express opsins has expanded dramatically in recent years. 55 Mice have been shown to express opsins in their skin, 15,56 as well as in their brain (Opn3 and Opn5), 57,58 testis (Opn5), 57 adipose tissue (Opn3), 59 vascular smooth muscle, 60,61 iris (Opn4), 62 and ciliary body (Opn5). 63 Recent work has suggested a photosensitive role for Opn3 in regulating metabolism in murine adipose tissue 59,64 and has demonstrated that Opn5 functions as a photopigment synchronizing circadian entrainment in skin in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The catalog of vertebrate tissues that have been found to express opsins has expanded dramatically in recent years. 55 Mice have been shown to express opsins in their skin, 15,56 as well as in their brain (Opn3 and Opn5), 57,58 testis (Opn5), 57 adipose tissue (Opn3), 59 vascular smooth muscle, 60,61 iris (Opn4), 62 and ciliary body (Opn5). 63 Recent work has suggested a photosensitive role for Opn3 in regulating metabolism in murine adipose tissue 59,64 and has demonstrated that Opn5 functions as a photopigment synchronizing circadian entrainment in skin in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cone and rod photopigments (Opn1 and Opn2) involved in purely visual functions relating to day/night vision and image forming processes, a wide range of non-visual opsins has been characterized in vertebrates over the last decades whose functions are not fully known (Peirson et al, 2009; Guido et al, 2010; Nagata et al, 2010; Terakita and Nagata, 2014; Leung and Montell, 2017; Dalesio et al, 2018); among these, Opn3, Opn4, and Opn5 are the most recently identified. In addition to mammals and other vertebrates (Bertolesi et al, 2014), ipRGCs expressing Opn4x and Opn4m were also shown to be present in chick retina (Contin et al, 2006, 2010; Diaz et al, 2014, 2016), appearing very early in development at E8 (Verra et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Sweet taste receptors were expressed in digestive tracts and regulated dietary sugar transport capacity, appetite, and insulin secretion in mice[47,48]. The sweet taste receptors were shown to be induced during adipocyte differentiation; further, the knockout mice of sweet taste receptors significantly reduced body weight and fat content[4951]. To test possible functions of Gr47b in adipose tissue, we knocked-down Gr47b fat-specifically, which significantly reduced body fat and recapitulated miR-969 GOF phenotype (Fig 6).…”
Section: Discussionmentioning
confidence: 99%